Perendaman Buah Margove Pedada (Sonneratia Caseolaris) dalam Pembuatan Permen Jelly - Illy, Wirahayu; Chaniago, Ramadhani; Wijayanti, Dwi; Basrin, Fitriani (Jurnal Agrotek Ummat, 2024)
The pedada type of mangrove fruit grows and develops a lot in coastal areas and has the potential to become processed food such as jelly candy because it contains sufficient fiber and vitamin C, but has a sour taste, unattractive physical properties such as color and texture, so it is necessary to improve the quality. his physique. This research aims to determine the immersion of the physical quality of pedada fruit jelly candy. This research used a Completely Randomized Design (CRD) with factorial, namely type of immersion (A): salt water, sugar water, whiting water and soaking time (L): 5 hours, 10 hours, 15 hours with 9 treatment combinations. The research variables are organoleptic tests for color, taste, aroma and texture. The results showed that the panelists preferred pedada fruit jelly candy soaked in sugar solution for 15 hours.